Identification of kinase modulators as host-directed therapeutics against intracellular methicillin-resistant Staphylococcus aureus - van den Biggelaar, Robin H. G. A.; Walburg, Kimberley V.; van den Eeden, Susan J. F.; van Doorn, Cassandra L. R.; Meiler, Eugenia; de Ries, Alex S.; Meijer, Annemarie H.; Ottenhoff, Tom H. M.; Saris, Anno (Frontiers in Cellular and Infection Microbiology, 2024)
The increasing prevalence of antimicrobial-resistant Staphylococcus aureus strains, especially methicillin-resistant S. aureus (MRSA), poses a threat to successful antibiotic treatment. Unsuccessful attempts to develop a vaccine and rising resistance to last-resort antibiotics urge the need for alternative treatments. Host-directed therapy (HDT) targeting critical intracellular stages of S. aureus emerges as a promising alternative, potentially acting synergistically with antibiotics and reducing the risk of de novo drug resistance. We assessed 201 ATP-competitive kinase inhibitors from Published Kinase Inhibitor Sets (PKIS1 and PKIS2) against intracellular MRSA. Seventeen hit compounds were identified, of which the two most effective and well-tolerated hit compounds (i.e., GW633459A and GW296115X) were selected for further analysis. The compounds did not affect planktonic bacterial cultures, while they were active in a range of human cell lines of cervical, skin, lung, breast and monocyte origin, confirming their host-directed mechanisms. GW633459A, structurally related to lapatinib, exhibited an HDT effect on intracellular MRSA independently of its known human epidermal growth factor receptor (EGFR)/(HER) kinase family targets. GW296115X activated adenosine monophosphate-activated protein kinase (AMPK), thereby enhancing bacterial degradation via autophagy. Finally, GW296115X not only reduced MRSA growth in human cells but also improved the survival rates of MRSA-infected zebrafish embryos, highlighting its potential as HDT.